Plant-Based Diets Are Not Enough? Understanding the Consumption of Plant-Based Meat Alternatives Along Ultra-processed Foods in Different Dietary Patterns in Germany - Ohlau, Marlene; Spiller, Achim; Risius, Antje (Frontiers in Nutrition, 2022)
A low-processive plant-based diet is considered valuable for a sustainable diet profile – it is supposed to meet health as well as environmental concerns. However, there is a growing trend towards plant-based meat alternatives, most of which are to be classified as ultra-processed food (UPF). The paper aimed to understand the consumption of different ultra-processed foods to describe their relation to dietary patterns and sustainability. The objective was (1) to depict the status-quo of consumption of plant-based meat alternatives along with other UPF groups (i.e., convenience products, fast foods, snacks, ultra-processed beverages) in a German sample (n=814) and (2) to investigate the extent to which all examined UPFs are represented in different dietary patterns (vegetarian, flexitarian, regular meat-eaters, high meat-eaters). UPF intake and dietary groups were determined using a food frequency questionnaire (FFQ). Potential factors influencing UPF consumption, such as attitudes toward sustainability and healthy eating practices, were assessed using validated and fitted psychometric scales. Overall, the frequency of UPF consumption varies significantly along the product groups studied. Plant-based meat alternatives were the least consumed food (12.3%), followed by convenience products (55.9%), fast foods (57.4%), ultra-processed beverages (80.1%), and sweet and salty snacks (97.3%). Plant-based meat alternative consumption predominated within a vegetarian diet, while other UPFs, like convenience products, fast foods, sweet and salty snacks, and ultra-processed beverages, were mainly consumed by meat-eaters. Remarkably, flexitarian diets depict low consumption of all types of ultra-processed foods. In order to meet societal sustainability goals, diets and corresponding societal and political actions should emphasize not only plant orientation but also the increase of non and low-processed foods.